I bambini dimenticati in auto e la questione dell’imputabilità. Considerazioni psichiatrico-forensi - Trevisan, Niccolò (Il sogno della farfalla, 2019)
By looking at the basic aspects of imputability in regards to the events of children abandoned in the car, this article aims at highlighting some new complex aspects. The most common diagnostic evaluation usually focuses on the presence of a dissociative amnesia at the moment of the event, suitable for a diminished responsibility. This is also in accordance with the neuroscientific approach which tends to assert an organic cause for any psychiatric pathology. By doing so, the causative role of the clinical aspects leading to the offence is diminished. The author proposes the introduction of some principle of the Human Birth Theory in the forensic-psychiatric practice. These could provide some innovative tools to psycho-dynamically identify and comprehend complex and apparently unexplainable events.